A meritorious integrated medical regimen for hepatic fibrosis and its complications via the systematic review and meta-analysis for Dahuang Zhechong pill-based therapy - Ye, Zhen; Huang, Qinfeng; She, Yingqi; Hu, Yu; Wu, Mingquan; Qin, Kaihua; Li, Linzhen; Zhang, Chuantao; Zuo, Xiaohong; Wei, Ailing; Mao, Dewen; Ye, Qiaobo (Frontiers in Medicine, 2022)
Background: Hepatic fibrosis is a health challenge due to the absence of satisfactory therapy, especially at the cirrhosis stage. Dahuang Zhechong pill (DHZCP)-based therapy is reportedly a successful treatment for hepatic fibrosis, and is even beneficial for the treatment of cirrhosis. Hence, a systematic review and clinical evidence assessment of DHZCP-based therapy should be performed, and clinical recommendations based on its efficacy for the treatment of hepatic fibrosis should be generated. With respect to potential indicators, the comparative value of hepatic function, spleen thickness, and portal vein internal diameter should be evaluated. Methods: PubMed, the Excerpta Medica Database, the Cochrane Library, Web of Science, the WanFang Database, the Chinese Scientific Journal Database, and the Chinese National Knowledge Infrastructure database were searched to identify clinical trials. Three subgroup analyses were performed based on stages of disease, medications use, and courses of treatment. Statistical analyses were performed using Review Manager 5.4. Results: A total of 18 studies including 1494 patients were evaluated. DHZCP-based therapy was effective in reducing plasma levels of hyaluronic acid, and laminin, procollagen III, and IV collagen were also reduced irrespective of hepatitis stage or the presence of hepatic cirrhosis. Abnormalities in alanine aminotransferase, aspartate aminotransferase, albumin, and total bilirubin were reversed. A 6 month course of treatment was the most beneficial DHZCP-based therapy regimen. Alanine aminotransferase improvement was more obvious in patients with cirrhosis, and alanine aminotransferase was reduced significantly in patients with hepatic cirrhosis. With respect to pharmacological mechanisms, DHZCP-based therapy could inhibit hepatic stellate cell growth and activation, reduce inflammation, and prevent extracellular matrix formation. Hepatic portal hypertension and splenomegaly were ameliorated significantly in the DHZCP-based therapy group. Conclusion: DHZCP-based therapy has demonstrated efficacy as a treatment for hepatic fibrosis, and cirrhosis. A 6-month course of treatment is the recommended option for DHZCP-based therapy in clinical practice. The combination of DHZCP-based therapy and entecavir is a favorable treatment for hepatic cirrhosis.